2015
DOI: 10.5455/jppa.20150221035635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excessive Green Tea Versus Fluoride and Caffeine on Body Weight and Serum Thyroid Hormones in Male Mice

Abstract: Green tea is a worldwide used beverage rich in fluoride and caffeine. To study the effect of excessive green tea intake versus fluoride and caffeine on body weight and serum thyroid hormones in male mice. Also, to confirm the effect of excessive green tea intake on thyroid gland was due to its fluoride and caffeine content or not. Thirty Male albino mice 25-30 gm weight were divided into five groups. Control (C) group (6 mice) receiving distilled water. Green tea (GT) treated group; 6 mice were given a 5 gm% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…At a concentration of below 0.5 mg/L, however, it is not an important factor for hypothyroidism in YGA. This finding confirms the results of other studies 10 – 16 , 30 . The mean of the TSH hormone level, according to different study variables, is demonstrated in Table 3 .…”
Section: Resultssupporting
confidence: 93%
“…At a concentration of below 0.5 mg/L, however, it is not an important factor for hypothyroidism in YGA. This finding confirms the results of other studies 10 – 16 , 30 . The mean of the TSH hormone level, according to different study variables, is demonstrated in Table 3 .…”
Section: Resultssupporting
confidence: 93%
“…On the contrary, prior researches (Chandra et al, 2011 ; Abulfadle et al, 2015 ) have declared that excessive and high doses of green tea have the potential to alter the thyroid gland physiology and architecture, that is, enlargement of thyroid gland as well as hypertrophy and/or hyperplasia of the thyroid follicles and inhibition of the activity of thyroid peroxidase and 50-deiodinase I with elevated thyroidal sodium-potassium- ATPase activity along with significant decrease in serum T3 and T4, and a parallel increase in serum thyroid stimulating hormone (TSH).…”
Section: Discussionmentioning
confidence: 87%